(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
the article reveals educational psychology or educational psychology - a branch of psychology that studies methods of teaching and upbringing that increase the efficiency of fulfilling educational tasks, the effectiveness of pedagogical measures, improving the psychological aspects of teaching, etc. Professional development occurs within the framework of one or another professional activity, which differs from general human development and personality development, a systemic characteristic of the mental development of a child of senior preschool age, which includes the formation of abilities and properties that provide the opportunity for him to carry out educational activities, as well as the adoption of the social position of the schoolchild.